The Family Talk Programme in Ireland: A Qualitative Analysis of the Experiences of Families With Parental Mental Illness - Mulligan, Christine; Furlong, Mairead; McGarr, Sharon; O'Connor, Siobhan; McGilloway, Sinead (Frontiers in Psychiatry, 2021)
Background Parental mental illness is common, costly, can lead to children developing mental disorders and impaired lifetime outcomes, and places a substantial burden on caregiving partners. Family Talk (FT) is a widely implemented, 7-session, whole-family programme, with promising evidence of effectiveness in targeting the intergenerational transmission of mental illness. However, to date, very little qualitative research of family experiences of FT has been undertaken. The objectives of this study were to: (1) investigate the experiences of families attending FT; and (2) explore the key facilitators and barriers to engagement in mainstream mental health settings. Methods This study was nested within a randomised controlled trial (RCT) of Family Talk (N=86 families [139 parents, 221 children]) implemented in 15 adult, child and primary care mental health sites in Ireland. Semi-structured interviews were conducted with a purposive sample of 45 participants, including 23 parents with mental illness (PMI), 7 partners and 15 children/young people aged 9 to 18 years. Interview data were transcribed verbatim and analysed using constructivist grounded theory. Results Over two thirds of families across sites reported substantial benefits from participation in FT, including reduced stigma, giving children and partners a voice, increased service-user confidence, and improved family communication/relationships. Key facilitators identified by families included: programme delivery by a competent, non-judgmental clinician; the whole-family approach; and family readiness to engage. Barriers to engagement included stigma, family crises/relapse, service constraints, impact of COVID-19, and a need for further child, family and follow-up sessions/supports. Conclusion This study is the first qualitative analysis of family experiences of FT to be conducted within the context of an RCT and national programme to introduce family-focused practice for families with PMI. The findings illustrate that FT is beneficial across cultural/policy contexts, different mental disorders and can be implemented across adult and child mental health settings, including children with existing mental health challenges. Key barriers and facilitators to implementation were identified by families, all of which should help to inform the future implementation of FT, and other similar interventions, both in Ireland and elsewhere.